Trabalhar na interface: coprodução de conhecimento entre cientistas e gestores públicos na saúde ambiental. O programa Vigiagua como estudo de caso em Santarém/PA - Louise Cavalcante; Stéphanie Nasuti (Confins)
Knowledge coproduction is process fostering to engage academic and extra-academic actors in the production of knowledge. In this context, this study aims to discuss the potential of a participatory approach called boundary work to mediate a process of knowledge coproduction between researchers and municipal public managers. In order to engage discussions about this process, the water quality of an Amazon region was used as the study object. The data was obtained through interviews and secondary data from public databases. The results indicate there are opportunities for knowledge coproduction for both researchers and managers. This new knowledge would have the potential to improve water management in Santarém, and thus, minimize the risks of waterborne diseases to which the population is subjected, and to support researchers in their research. In this case, the process shows itself as a win-win relationship, there are some limitations to its effective realization, such as the geographic distance of the actors involved, lack of laboratories infrastructure, data communication channel and the academic and management institutional intrinsic characteristics.